Identification of Gene Diversity of Melanocortin 4 Receptor for Commercial Rabbit Breeds - Kamila, Firda Tasya; Kamalludin, Mamat Hamidi; Sutopo, Sutopo; Lestari, Dela Ayu; Setiatin, Enny Tantini; Agustine, Ananda Dwi; Latifa, Alfa Putri; Nabilah, Zata; Philco, Syaddad Verahry; Setiaji, Asep (Buletin Peternakan, 2025)
Molecular genetic markers are regularly implemented in rabbit management for better breeding by selecting for specific genotypes. This study aimed to examine the diversity of the melanocortin-4 receptor gene in rabbits in Central Java, Indonesia. A total of 35 bucks were used in this study, comprising 10 New Zealand White, 11 Hyla and 14 Hycole. The DNA was extracted by Gene JET Whole Blood Genomic DNA extraction kit. Single Nucleotide Polymorphism (SNP) was detected by Polymerase Chain Reaction (PCR) and DNA sequencing. Hot carcass weight, cold carcass weight, reference weight and cut point 1-5 weight were among the parameters that were measured. This study showed that Melanocortin 4 Receptor (MC4R) genes were polymorphic, containing missense mutations and one SNP at 519G→A SNP 519GA had two alleles, A and G, with three genotypes (AA, GG, and AG). The rabbit population did not achieve HardyWeinberg Equilibrium (HWE) and showed a low level of genetic diversity as indicated by the heterozygosity results. The result of this study concluded that the frecuency AG as a genotype was higher than either GG or AA and A had a higher allele frequency than G. We recommended improving the validity of the data across various rabbit populations